A MXene / vanadium dioxide / melamine foam composite material and its preparation method and application

Through the use of MXene/vanadium dioxide/melamine foam composites, the problem of unadjustable infrared emissivity of existing infrared stealth materials has been solved, and the adjustability of infrared emissivity and improvement of infrared stealth performance has been achieved.

CN119219977BActive Publication Date: 2025-04-01SHANGHAI GER ADVANCE MATERIAL SEC&TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411730022.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-01
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The infrared emissivity of existing infrared stealth materials is unadjusted, which limits its further development in the field of infrared stealth.

Method used

The MXene/vanadium dioxide/melamine foam composite material is used to adjust the infrared emissivity through the phase transition of vanadium dioxide, and the porous structure of melamine foam increases the specific surface area to achieve adjustability of infrared stealth performance.

Benefits of technology

It realizes the adjustability of infrared emissivity, improves infrared stealth performance, and maintains excellent stealth effect in complex temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219977B_ABST
    Figure CN119219977B_ABST
Patent Text Reader

Abstract

The present invention relates to a MXene / vanadium dioxide / melamine foam composite material and a preparation method and application thereof. The MXene / vanadium dioxide / melamine foam composite material prepared by the present invention has a very superior infrared stealth performance compared with the performance of the foam infrared stealth material synthesized by the existing method, and the phase change particles can control the infrared emissivity of the foam composite material by changing the temperature, so as to prepare a MXene / vanadium dioxide / melamine foam composite material with adjustable infrared stealth performance, which can protect the detected object from being discovered by the infrared detector in a complex temperature environment. The adjustable infrared stealth material prepared by the present invention is helpful to expand the application of foam composite materials in the fields of infrared stealth, high-precision national defense and military industry. The MXene / vanadium dioxide / melamine foam composite material prepared by the present invention is in a foamy state, light in weight and high in strength. The present invention can be used in the fields of controllable infrared stealth and heat storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a MXene / vanadium dioxide / melamine foam composite material and a preparation method and application thereof. Background Art

[0002] In today's information age, it is very important to hide one's own information while obtaining information from the other party. This is especially important in the field of military defense, and infrared detection is one of the most conventional detection methods. However, the existing various infrared stealth materials have certain limitations. Therefore, the development of infrared stealth materials with adjustable emissivity is of great significance.

[0003] Titanium carbide MXene is a new type of transition metal carbide material that has emerged in recent years. It has a unique two-dimensional planar structure, rich functional groups on the surface, and some metal-like properties, providing the characteristics of low infrared emissivity. It has achieved many research results in the field of infrared stealth. However, in the existing technology, titanium carbide MXene is used as a stealth material and its infrared emissivity does not change after being made into a device, which greatly limits its further development in the field of infrared stealth.

[0004] Chinese patent CN110257019B discloses a phase change composite material with photothermal conversion function and its preparation method, which combines Ti2O3 nanoparticles with heat storage phase change materials to prepare multifunctional phase change composite materials, in order to give it photothermal conversion performance on the basis of phase change heat storage and temperature control functions, and provide a carbon foam-based phase change composite material that is easy to cut and process, has controllable appearance size, is lightweight and flexible, and has photothermal conversion performance. Phase change composite materials have a three-dimensional porous carbon foam matrix, and the system can stably store phase change materials, and the storage capacity is adjustable. It has excellent photothermal conversion and temperature regulation effects, and can be used for thermal energy storage and release, thermal insulation, photothermal conversion, infrared stealth and false indication of military equipment, etc. This patent solution requires high-temperature carbonization to obtain carbon foam to obtain photothermal performance. Its stealth is achieved by utilizing the energy storage characteristics of phase change materials. Energy storage has an upper limit and limitations.

[0005] Chinese patent CN109181650B discloses a dynamic thermal infrared stealth composite material based on dual phase change and a preparation method; in particular, it refers to a VO2 / mica-based phase change heat storage thin layer composite material and a preparation method; the VO2 / mica-based phase change heat storage thin layer composite material is composed of a VO2 nanoparticle coating and a mica-based phase change heat storage thin layer, and the mica-based phase change heat storage thin layer is composed of stearic acid and a mica matrix after vanadium extraction in a mass ratio of 3~5:5~7. VO2 nanoparticles are prepared by extracting vanadium from vanadium mica using a roasting acid leaching process, and a mica-based phase change heat storage thin layer is prepared by embedding a phase change functional body with mica after vanadium extraction as a supporting matrix, and VO2 nanoparticles are coated on the mica-based phase change heat storage thin layer to obtain a dual phase change composite material. The dynamic thermal infrared stealth composite material based on dual phase change can achieve synergistic enhancement of thermal infrared stealth performance and can be applied to thermal infrared stealth technology. This scheme only uses phase change materials to achieve thermal infrared stealth capability, and passively absorbs heat to achieve phase change. Summary of the invention

[0006] The purpose of the present invention is to solve the problem of non-adjustable emissivity of stealth materials in the prior art, and to provide a MXene / vanadium dioxide / melamine foam composite material and a preparation method and application thereof.

[0007] The MXene / vanadium dioxide / melamine foam composite material provided in the present application has an infrared stealth property that can change the infrared emissivity.

[0008] The purpose of the present invention can be achieved by the following technical solutions:

[0009] The present invention first provides a method for preparing a MXene / vanadium dioxide / melamine foam composite material, the method comprising the following steps:

[0010] (1) Preparation of single-layer titanium carbide MXene powder: Ti3AlC2MAX phase, lithium fluoride and hydrochloric acid are mixed and etched, washed to neutrality, and the supernatant is collected by ultrasonication and centrifugation to obtain a single-layer titanium carbide MXene dispersion, which is placed in a freezer and frozen, and then freeze-dried to obtain a single-layer titanium carbide MXene powder;

[0011] (2) Preparation of vanadium dioxide / titanium carbide MXene mixed dispersion: Mix vanadium pentoxide and dihydrated oxalic acid for hydrothermal reduction, wash and dry to obtain vanadium dioxide powder, dissolve vanadium dioxide and titanium carbide MXene in deionized water, stir and ultrasonicate to obtain vanadium dioxide / titanium carbide MXene mixed dispersion;

[0012] (3) Preparation of MXene / vanadium dioxide / melamine foam composite material: The melamine foam is washed with ethanol, dried, and then immersed in a vanadium dioxide / titanium carbide MXene mixed dispersion. After being taken out, it is immediately placed in a freezer and frozen. Finally, the solvent is removed by a freeze dryer to obtain a MXene / vanadium dioxide / melamine foam composite material. In the MXene / vanadium dioxide / melamine foam composite material, the melamine foam is a layered structure, and the MXene and vanadium dioxide are attached to the surface and internal gaps of the melamine foam.

[0013] In one embodiment of the present invention, in step (1), the molar ratio of Ti3AlC2MAX phase, lithium fluoride and hydrochloric acid is 1:12:3.6.

[0014] In one embodiment of the present invention, in step (1), the ultrasonic condition is 150-350 W of power for 90-270 min.

[0015] In one embodiment of the present invention, in step (1), the centrifugal speed condition is 3000~5000rpm.

[0016] In one embodiment of the present invention, in step (1), the temperature of the freezer is -70 to -80°C, and the freezing time is 6 to 12 h; the freeze-drying temperature is -30 to -40°C, and the drying time is 60 to 72 h.

[0017] In one embodiment of the present invention, in step (2), the molar ratio of vanadium pentoxide to oxalic acid dihydrate is 1:(1-3).

[0018] In one embodiment of the present invention, in step (2), the hydrothermal conditions are a temperature of 250-300° C. and a time of 24-48 hours.

[0019] In one embodiment of the present invention, in step (2), the mass ratio of titanium carbide MXene to vanadium dioxide is 1:(1-5), and after vanadium dioxide and titanium carbide MXene are dissolved in deionized water, the total concentration of vanadium dioxide and titanium carbide MXene is 0.04-0.1 g / ml.

[0020] In one embodiment of the present invention, in step (2), the stirring and ultrasonic conditions are: 700-1200 rpm, stirring for 60-120 min, and 150-350 W ultrasonic for 60-120 min.

[0021] In one embodiment of the present invention, in step (3), when the melamine foam is immersed in the vanadium dioxide / titanium carbide MXene mixed dispersion, the volume of the melamine foam is calculated as follows: 3The volume of the vanadium dioxide / titanium carbide MXene mixed dispersion impregnated in the melamine foam is 1-5 ml.

[0022] For example, the size of the melamine foam is 25 × 25 × 2 mm, and the amount of the vanadium dioxide / titanium carbide MXene mixed dispersion is 1.25 ml.

[0023] In one embodiment of the present invention, in step (3), the melamine foam is immersed in the vanadium dioxide / titanium carbide MXene mixed dispersion for 1 to 3 hours.

[0024] In one embodiment of the present invention, in step (3), the temperature of the freezer is -70 to -80°C, and the freezing time is 6 to 12 hours.

[0025] In one embodiment of the present invention, in step (3), the temperature of the freeze dryer is -30 to -40°C, and the drying time is 60 to 72 hours.

[0026] The present invention further provides a MXene / vanadium dioxide / melamine foam composite material, which is prepared by the above method.

[0027] Preferably, the MXene / vanadium dioxide / melamine foam composite material is in a foam state.

[0028] The present invention further provides an application of the MXene / vanadium dioxide / melamine foam composite material, wherein the MXene / vanadium dioxide / melamine foam composite material is used to prepare an infrared stealth material. The obtained infrared stealth material has the property of adjustable infrared emissivity.

[0029] In the scheme of the present invention, on the basis of titanium carbide MXene, the phase change material vanadium dioxide is introduced to adjust its emissivity, and melamine foam is further introduced. The porous structure of melamine foam can provide many binding sites so that titanium carbide MXene and vanadium dioxide are mixed and attached to the foam skeleton. The two-dimensional titanium carbide MXene and the zero-dimensional vanadium dioxide particles are combined and attached to the foam skeleton, which greatly increases the specific surface area. The ability of the MXene / vanadium dioxide / melamine foam composite material to adjust the infrared emissivity comes from the phase transition of vanadium dioxide. After the phase transition, vanadium dioxide changes from a monoclinic insulator to a goldstone conductor. At this time, its emissivity drops significantly, so that the infrared stealth material can have a better stealth performance.

[0030] The MXene / vanadium dioxide / melamine foam composite material prepared by the present invention has a very superior infrared stealth performance compared with the performance of the foam infrared stealth material synthesized by the existing method, and the phase change particles can control the infrared emissivity of the foam composite material by changing the temperature, so as to prepare a MXene / vanadium dioxide / melamine foam composite material with adjustable infrared stealth performance, which can protect the detected object from being discovered by the infrared detector in a complex temperature environment. The adjustable infrared stealth material prepared by the present invention is helpful to expand the application of foam composite materials in the fields of infrared stealth, high-precision national defense and military industry. The MXene / vanadium dioxide / melamine foam composite material prepared by the present invention is in a foamy state, light in weight and high in strength. The present invention can be used in the fields of controllable infrared stealth and heat storage.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The structure of the melamine foam in the present invention not only provides abundant sites for the attachment of titanium carbide MXene and vanadium dioxide, but also the cavity structure provides certain thermal insulation performance, which can further improve the infrared stealth performance (because its temperature is reduced, the difference with the ambient temperature is also reduced, thereby achieving infrared stealth).

[0033] 2. The metallic structure of the titanium carbide MXene in the present invention gives the foam composite material an initial lower infrared emissivity (at the same temperature, objects with low emissivity radiate lower infrared energy). At the same time, its excellent photothermal and electrical conductivity can give vanadium dioxide the energy for phase change, and enable the foam composite material to disguise a cold object as a hot object (heating by light or electricity, if the ambient temperature is higher than the object, this method can be used to achieve consistency with the ambient temperature).

[0034] 3. The vanadium dioxide in the present invention has a phase transition from an insulator to an electrical conductor. According to the Hagen-Rubens law, the change in conductivity gives the foam composite material a change in infrared emissivity (the infrared emissivity of the material is negatively correlated with the conductivity, so the better the conductivity, the lower the emissivity). When the temperature changes, the phase change absorbs heat and the optimization of conductivity can enable the foam composite material to still maintain excellent stealth performance (when the temperature rises, the vanadium dioxide phase changes, absorbs part of the energy, and reduces the infrared emissivity, which can make the infrared temperature lower than the actual temperature, thereby achieving stealth).

[0035] 4. The MXene / vanadium dioxide / melamine foam composite material prepared by the present invention utilizes the change in conductivity before and after the phase transition of vanadium dioxide to regulate infrared emissivity, which is of great significance for intelligent infrared stealth and can be applied in the military and national defense fields.

[0036] 5. The composite material prepared in this application has the thermal insulation of melamine foam and the photothermal and low-emission properties of MXene. It can actively achieve phase change through photothermal or electrothermal means, which is more controllable. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 This is a scanning electron microscope image of the MXene / vanadium dioxide / melamine foam composite material in Example 1.

[0039] Figure 2 The infrared images and temperature curves of the MXene / vanadium dioxide / melamine foam composite material in Example 1 at different background temperatures and the change curve of infrared emissivity. DETAILED DESCRIPTION

[0040] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0041] Example 1

[0042] This embodiment provides a method for preparing a MXene / vanadium dioxide / melamine foam composite material with adjustable infrared emissivity, which is carried out according to the following steps.

[0043] (1) Preparation of single-layer titanium carbide MXene dispersion: 10 mL of deionized water and 30 mL of hydrochloric acid were mixed in a Teflon-lined reactor, 2.0 g of Ti3AlC2MAX phase and 3.2 g of lithium fluoride were added, and then stirred in an oil bath at 37°C and etched for 24 h. After etching, the mixture was washed with deionized water until pH = 7, and then the aqueous solution was placed in an ultrasonic machine at a power of 200 W for 120 min to separate the multilayer MXene into a single layer, and the upper layer of liquid was separated by centrifugation at 3500 rpm, and then placed in a freezer at -80°C for 6 h, and dried in a freeze dryer at -35°C for 65 h to obtain a single-layer titanium carbide MXene;

[0044] (2) Preparation of vanadium dioxide / titanium carbide MXene mixed dispersion: 1.82 g of vanadium pentoxide and 2.52 g of oxalic acid dihydrate were dissolved in 60 mL of deionized water, poured into a hydrothermal reactor and placed in a digital display electric heating blast drying oven for reaction at 250 ° C for 48 h, washed with deionized water and anhydrous ethanol respectively, placed in a vacuum drying oven at 60 ° C for 12 hours to obtain VO2 particles, 100 mg of the single-layer titanium carbide MXene obtained in step (1) and 200 mg of vanadium dioxide were dissolved in 5 mL of water, and stirred at 1000 rpm for 120 min to obtain a vanadium dioxide / titanium carbide MXene mixed dispersion;

[0045] (3) Preparation of MXene / vanadium dioxide / melamine foam composite material: 25×25×2 mm melamine foam was washed with ethanol, dried, and immersed in the vanadium dioxide / titanium carbide MXene mixed dispersion obtained in step (2). After 2 h, it was taken out and immediately placed in a freezer at -80 °C for 6 h. Finally, it was dried in a freeze dryer at -35 °C for 65 h to remove the solvent, thereby obtaining a MXene / vanadium dioxide / melamine foam composite material.

[0046] This embodiment uses melamine foam as a skeleton, and uses low-temperature freeze-drying technology to attach two-dimensional titanium carbide MXene and zero-dimensional vanadium dioxide to the skeleton. While using the cavity structure of the foam itself for heat insulation, the initial low infrared emissivity of titanium carbide MXene and the reduced emissivity caused by the phase change of vanadium dioxide are used to achieve controllable infrared stealth capability.

[0047] The infrared images and temperature curves of the MXene / vanadium dioxide / melamine foam composite material obtained in this example at different background temperatures and the change curves of the infrared emissivity are shown in the figure below. Figure 2 As shown, the foam composite material is placed on a hot table, and a thermocouple is used to test the actual temperature of the hot table surface, the foam surface, and the temperature difference between the two (the temperature difference represents the thermal insulation performance of the foam structure), and the temperature-time curve is obtained as shown in Figure 2 b. At the same time, a portable infrared camera is used to capture the infrared temperature of the foam surface. The image is as follows: Figure 2 As shown in a, the infrared color tends to be consistent, the temperature changes little, and the infrared temperature is collected and the temperature-time curve is drawn. Figure 2 b. It can be seen that the infrared temperature is lower than the actual temperature and has a large change around 60°C. At this time, the emissivity decreases and the infrared temperature is much lower than the actual temperature. The infrared temperature is obtained by calculating its emissivity. Figure 2 c shows the relationship between its emissivity and temperature.

[0048] When the MXene / vanadium dioxide / melamine foam composite material prepared by the present invention is covered on an object, it can maintain similar colors in infrared images within a wide temperature range of 30-90°C, and show consistency in infrared images. This is attributed to the fact that the emissivity of the foam composite material decreases significantly after the temperature reaches about 60°C (the emissivity can be directly measured by an instrument or calculated using the actual temperature and the infrared temperature, the data is referenced to Figure 2 ), so that the infrared temperature is maintained in a relatively stable state. The prepared MXene / vanadium dioxide / melamine foam composite material can be used in the field of infrared stealth.

[0049] The scanning electron microscope image of the MXene / vanadium dioxide / melamine foam composite material obtained in this example is as follows: Figure 1 shown.

[0050] Example 2

[0051] This embodiment provides a method for preparing a MXene / vanadium dioxide / melamine foam composite material with adjustable infrared emissivity, which is carried out according to the following steps.

[0052] (1) Preparation of single-layer titanium carbide MXene dispersion: 10 mL of deionized water and 30 mL of hydrochloric acid were mixed in a Teflon-lined reactor, 2.0 g of Ti3AlC2MAX phase and 3.2 g of lithium fluoride were added, and then stirred in an oil bath at 37°C and etched for 24 h. After etching, the mixture was washed with deionized water until pH = 7, and then the aqueous solution was placed in an ultrasonic machine at a power of 350 W for 90 min to separate the multilayer MXene into a single layer, and the upper layer of liquid was separated by centrifugation at 5000 rpm, and then placed in a freezer at -70°C for 12 h, and dried in a freeze dryer at -30°C for 72 h to obtain a single-layer titanium carbide MXene;

[0053] (2) Preparation of vanadium dioxide / titanium carbide MXene mixed dispersion: 1.82 g of vanadium pentoxide and 2.52 g of oxalic acid dihydrate were dissolved in 60 mL of deionized water, poured into a hydrothermal reactor and placed in a digital display electric heating blast drying oven for reaction at 300 °C for 24 h, washed with deionized water and anhydrous ethanol respectively, and dried in a vacuum drying oven at 60 °C for 12 h to obtain VO2 particles. 100 mg of titanium carbide and 100 mg of vanadium dioxide were dissolved in 5 mL of water and stirred at 700 rpm for 150 min to obtain a vanadium dioxide / titanium carbide MXene mixed dispersion;

[0054] (3) Preparation of MXene / vanadium dioxide / melamine foam composite material: 25×25×2 mm melamine foam was washed with ethanol, dried, and immersed in the vanadium dioxide / titanium carbide MXene mixed dispersion obtained in step (2). After 2 h, it was taken out and immediately placed in a freezer at -70°C for 12 h. Finally, it was dried in a freeze dryer at -30°C for 72 h to remove the solvent, thereby obtaining a MXene / vanadium dioxide / melamine foam composite material.

[0055] The MXene / vanadium dioxide / melamine foam composite material obtained in this example was tested for infrared stealth capability in the same way. The infrared images at a background temperature of 30-85°C tended to be consistent, indicating good stealth performance. At the same time, at a temperature of about 60°C, the infrared emissivity changed from 0.57 to 0.32.

[0056] Example 3

[0057] This embodiment is a method for preparing a MXene / vanadium dioxide / melamine foam composite material with adjustable infrared emissivity, which is carried out according to the following steps.

[0058] (1) Preparation of single-layer titanium carbide MXene dispersion: 10 mL of deionized water and 30 mL of hydrochloric acid were mixed in a Teflon-lined reactor, 2.0 g of Ti3AlC2MAX phase and 3.2 g of lithium fluoride were added, and then stirred in an oil bath at 37°C and etched for 24 h. After etching, the mixture was washed with deionized water until pH = 7, and then the aqueous solution was placed in an ultrasonic machine at a power of 200 W for 120 min to separate the multilayer MXene into a single layer, and the upper layer of liquid was separated by centrifugation, and then placed in a freezer at -75°C for 9 h, and dried in a freeze dryer at -40°C for 60 h to obtain a single-layer titanium carbide MXene;

[0059] (2) Preparation of vanadium dioxide / titanium carbide MXene mixed dispersion: 1.82 g of vanadium pentoxide and 2.52 g of oxalic acid dihydrate were dissolved in 60 mL of deionized water, poured into a hydrothermal reactor and placed in a digital display electric heating blast drying oven for reaction at 275 °C for 36 h, washed with deionized water and anhydrous ethanol respectively, placed in a vacuum drying oven at 60 °C for 12 hours to obtain VO2 particles, 100 mg of titanium carbide and 200 mg of vanadium dioxide were dissolved in 5 mL of water, and stirred at 1200 rpm for 90 min to obtain a vanadium dioxide / titanium carbide MXene mixed dispersion;

[0060] (3) Preparation of MXene / vanadium dioxide / melamine foam composite material: 25×25×2 mm melamine foam was washed with ethanol, dried, and immersed in the vanadium dioxide / titanium carbide MXene mixed dispersion obtained in step (2). After 2 h, it was taken out and immediately placed in a freezer at -75°C for 9 h. Finally, it was dried in a freeze dryer at -40°C for 60 h to remove the solvent, thereby obtaining a MXene / vanadium dioxide / melamine foam composite material.

[0061] The MXene / vanadium dioxide / melamine foam composite material obtained in this example was tested for infrared stealth capability in the same way. The infrared images at background temperatures of 35 to 90°C tended to be consistent, indicating good stealth performance. At the same time, at a temperature of about 60°C, the infrared emissivity changed from 0.67 to 0.35.

[0062] Example 4

[0063] This embodiment is a method for preparing a MXene / vanadium dioxide / melamine foam composite material with adjustable infrared emissivity. The difference between this embodiment and embodiment 1 is that the mass of vanadium dioxide in step (2) is 300 mg, and the other steps are the same.

[0064] The MXene / vanadium dioxide / melamine foam composite material obtained in this example was tested for infrared stealth capability in the same way. The infrared images at a background temperature of 35-85°C tended to be consistent, showing good stealth performance. At the same time, at a temperature of about 60°C, the infrared emissivity changed from 0.70 to 0.32.

[0065] Example 5

[0066] This embodiment is a method for preparing a MXene / vanadium dioxide / melamine foam composite material with adjustable infrared emissivity. The difference between this embodiment and Example 1 is that the mass of vanadium dioxide in step (2) is 400 mg, and the other steps are the same.

[0067] The MXene / vanadium dioxide / melamine foam composite material obtained in this example was tested for infrared stealth capability in the same way. The infrared images at a background temperature of 35-75°C tended to be consistent, indicating good stealth performance. At the same time, at a temperature of about 60°C, the infrared emissivity changed from 0.72 to 0.38.

[0068] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0069] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a MXene / vanadium dioxide / melamine foam composite material, characterized in that: The method comprises the following steps: (1) Preparation of single-layer titanium carbide MXene powder: Ti3AlC2MAX phase, lithium fluoride and hydrochloric acid are mixed and etched, washed to neutrality, and the supernatant is collected by ultrasonication and centrifugation to obtain a single-layer titanium carbide MXene dispersion, which is placed in a freezer and frozen, and then freeze-dried to obtain a single-layer titanium carbide MXene powder; (2) Preparation of vanadium dioxide / titanium carbide MXene mixed dispersion: Mix vanadium pentoxide and dihydrated oxalic acid for hydrothermal reduction, wash and dry to obtain vanadium dioxide powder, dissolve vanadium dioxide and titanium carbide MXene in deionized water, stir and ultrasonicate to obtain vanadium dioxide / titanium carbide MXene mixed dispersion; (3) Preparation of MXene / vanadium dioxide / melamine foam composite material: The melamine foam is washed with ethanol, dried, and then immersed in a vanadium dioxide / titanium carbide MXene mixed dispersion. After being taken out, it is immediately placed in a freezer and frozen. Finally, the solvent is removed by a freeze dryer to obtain a MXene / vanadium dioxide / melamine foam composite material. In the MXene / vanadium dioxide / melamine foam composite material, the melamine foam is a layered structure, and the MXene and vanadium dioxide are attached to the surface and internal gaps of the melamine foam.

2. The method for preparing a MXene / vanadium dioxide / melamine foam composite material according to claim 1, characterized in that: In step (1), the molar ratio of Ti3AlC2MAX phase, lithium fluoride and hydrochloric acid is 1:12:3.

6.

3. The method for preparing a MXene / vanadium dioxide / melamine foam composite material according to claim 1, characterized in that: In step (1), the ultrasonic condition is 150~350W power for 90~270min; in step (1), the centrifugal speed condition is 3000~5000rpm; in step (1), the temperature of the freezer is -70~-80℃, and the freezing time is 6~12h; the freeze-drying temperature is -30~-40℃, and the drying time is 60~72h.

4. The method for preparing a MXene / vanadium dioxide / melamine foam composite material according to claim 1, characterized in that: In step (2), the molar ratio of vanadium pentoxide to oxalic acid dihydrate is 1:(1-3).

5. The method for preparing a MXene / vanadium dioxide / melamine foam composite material according to claim 1, characterized in that: In step (2), the hydrothermal conditions are a temperature of 250-300° C. and a time of 24-48 h.

6. The method for preparing a MXene / vanadium dioxide / melamine foam composite material according to claim 1, characterized in that: In step (2), the mass ratio of titanium carbide MXene to vanadium dioxide is 1:(1-5). After vanadium dioxide and titanium carbide MXene are dissolved in deionized water, the total concentration of vanadium dioxide and titanium carbide MXene is 0.04-0.1 g / ml.

7. The method for preparing a MXene / vanadium dioxide / melamine foam composite material according to claim 1, characterized in that: When melamine foam is immersed in the vanadium dioxide / titanium carbide MXene mixed dispersion, based on the volume of melamine foam, per 1000 mm 3 The volume of the vanadium dioxide / titanium carbide MXene mixed dispersion impregnated in the melamine foam is 1-5 ml.

8. The method for preparing a MXene / vanadium dioxide / melamine foam composite material according to claim 1, characterized in that: In step (3), the melamine foam is immersed in the vanadium dioxide / titanium carbide MXene mixed solution for 1 to 3 hours; In step (3), the temperature of the freezer is -70 to -80°C, and the freezing time is 6 to 12 hours; In step (3), the temperature of the freeze dryer is -30~-40°C, and the drying time is 60~72 h.

9. A MXene / vanadium dioxide / melamine foam composite material, characterized in that: The method is prepared by any one of claims 1 to 8.

10. An application of the MXene / vanadium dioxide / melamine foam composite material according to claim 9, characterized in that: The MXene / vanadium dioxide / melamine foam composite material is used to prepare infrared stealth material.

Citation Information

Patent Citations

  • A dynamic thermal infrared stealth composite material based on dual phase transition and its preparation method

    CN109181650B

  • A phase change composite material with photothermal conversion function and its preparation method

    CN110257019B

  • Preparation method for thermally-induced infrared-emission-rate-variable vanadium dioxide thin sheet

    CN105669194A

  • Process for producing lithium batteries having an ultra-high energy density

    CN108140786A